DESAIN DAN ANALISIS AKURASI ALAT UKUR KETINGGIAN AIR DI SUNGAI UNTUK SISTEM PERINGATAN DINI BENCANA BANJIR BERBASIS INTERNET OF THINGS - Utama, Yoga Alif Kurnia; P. Kolago, Demison (Universitas Sangga Buana, 2024)
Climate change and the growing need for water resources have driven increased attention to the monitoring and management of rivers and other water sources. River water level is one of the important parameters in monitoring water quality and quantity, as well as in understanding the dynamics of river ecosystems. Therefore, the development of reliable, accurate, and high-technology-based water level measuring instruments is an urgent need. This research will create a system that can detect river water levels periodically using A01NYUB sensors. This water level data will be sent to a website using the internet network via GSM Modem. The results show that the A01NYUB sensor has a measurement error of 0.26% and a standard deviation of 0.43%. This proves that the A01NYUB sensor can be used for flood early warning systems because it has a measurement error and a fairly small standard deviation.